Excellent Service in Increasing Customer Satisfaction: Strategy and Implementation in the Digital Era - Langitan, Seska Vonny (International Journal of Education, Information Technology, and Others, 2025)
Excellent service is the main key in winning business competition, especially in the digital era which demands speed, accuracy and empathy. This article discusses the concept of excellent service, its supporting factors, as well as strategic implementation that can be implemented by organizations to increase customer satisfaction and loyalty. This research uses a descriptive qualitative approach through literature study. The study results show that excellent service must involve elements of tangibility, reliability, responsiveness, assurance and empathy which are integrated with digital technology to provide an optimal customer experience.